STRATEGI PENGEMBANGAN USAHA TEPUNG SAGU DI KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI - Irma Nurhayati; Sumarno Sumarno; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study is to analyze the business development strategy of corn starch in Tebing Tinggi Barat District of Meranti Regency. This study was conducted in Tebing Tinggi Barat District of Meranti Regency. The sample is corn starch business owners in the district of Tebing Tinggi Barat. The total sample of this study is four factories. The data collected by obseravation and interview. The data analyz technique using SWOT analysis to established a table of Internal Factor Analysis Summary (IFAS) and Eksternal Factor Analysis Summary EFAS. The results showed that the corn starch business in the District of Tebing Tinggi Barat Meranti Regency has a strength and a large market opportunity. Enterprises of the corn starch should maintain and enhance the strength to take the market opportunities that exist. The strategy that should be implemented by businesses corn starch is SO strategy known as an aggressive strategy. The aggressive strategy is using strength to take advantage the opportunities. Keywords : SWOT Analysis, Business Strategy, Corn Starch.